Anti-fouling and anti-corrosion coating based on quantum dot material as well as preparation method and application thereof

By using quantum dot materials such as copper sulfide, zinc sulfide, cadmium sulfide, etc. in the coating, combined with organic bonding resin and curing agent to form a dense coating, the existing coating has poor anti-corrosion and anti-fouling effects. The problem is that more stable protection effect and longer service life are achieved.

CN119264782APending Publication Date: 2025-01-07CHANGJIANG RIVER SCI RES INST CHANGJIANG WATER RESOURCES COMMISSION +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411591293.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing coatings have poor corrosion and anti-fouling effects in marine environments, and are prone to microscopic defects such as pores and cracks, resulting in unstable protective effects and affecting the service life of hydraulic buildings and marine equipment.

Method used

Adopt anti-fouling and anti-corrosion coatings based on quantum dot materials, including organic bonding resins, curing agents and quantum dot materials. Quantum dot materials include copper sulfide, zinc sulfide, cadmium sulfide, etc., and through specific mass ratios and preparation methods, denseness is formed. Coatings to improve corrosion and stain resistance.

Benefits of technology

It significantly improves the anti-corrosion and anti-fouling properties of the coating, extends the service life, reduces the secondary pollution of quantum dot materials to the environment, and provides stable protective effects. It is suitable for hydraulic buildings and marine equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264782A_ABST
    Figure CN119264782A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-fouling and anti-corrosion coating based on a quantum dot material as well as a preparation method and application thereof, and relates to the technical field of corrosion and biological fouling control of hydraulic structures and marine equipment materials. The anti-fouling and anti-corrosion coating based on the quantum dot material comprises organic bonding resin, a curing agent and the quantum dot material, and the mass ratio of the organic bonding resin to the curing agent to the quantum dot material is (3-5): (5-7): (0.005-0.05); wherein the quantum dot material comprises at least one of a copper sulfide quantum dot material, a zinc sulfide quantum dot material, a cadmium sulfide quantum dot material and a composite quantum dot material, and the particle size of the copper sulfide quantum dot material, the zinc sulfide quantum dot material and the cadmium sulfide quantum dot material is smaller than 20 nm. The coating provided by the technical scheme of the invention has excellent anti-corrosion and anti-fouling effects and relatively long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydraulic structures, marine equipment material corrosion and biological fouling control, and in particular to an antifouling and anticorrosion coating based on quantum dot materials, and a preparation method and application thereof. Background Art

[0002] Biological fouling is common on the surfaces of facilities in rivers, lakes and marine environments, such as hydraulic structures, aquaculture cages, pipelines, large offshore platforms, submarine cables and ships. Biological fouling can significantly increase the resistance of water pipes and channels, reduce water delivery efficiency; affect the opening and closing and sealing of gates; block aquaculture cages, resulting in a decrease in aquaculture production; increase the resistance of ships, resulting in increased fuel consumption and reduced navigation speed. During the growth of fouling organisms, they will secrete a large amount of acidic substances that corrode the surface of metals and concrete, accelerate the corrosion of building materials, ships and other marine equipment, and bring serious safety hazards to water conservancy projects and marine equipment. The corrosion of metal materials in the marine environment is also an extremely serious problem.

[0003] Coating is currently a commonly used method for biofouling and corrosion protection. Coating forms a protective barrier on substrates such as metals and concrete, preventing corrosive media such as water and oxygen from diffusing to the surface of the material. However, after coating, microscopic defects such as pores and cracks are inevitably present inside the coating. In addition, in actual service environments, it is prone to failure problems such as swelling, cracking, and peeling, which affect the protective effect of the coating. Summary of the invention

[0004] The main purpose of the present invention is to propose an anti-fouling and anti-corrosion coating based on quantum dot materials and a preparation method and application thereof, aiming to solve the problem that the existing coatings have poor anti-corrosion and anti-fouling effects.

[0005] To achieve the above-mentioned object, the present invention provides an antifouling and anticorrosion coating based on quantum dot materials, comprising an organic binder resin, a curing agent and a quantum dot material, wherein the mass ratio of the organic binder resin, the curing agent and the quantum dot material is (3-5): (5-7): (0.005-0.05);

[0006] Among them, the quantum dot material includes at least one of copper sulfide quantum dot material, zinc sulfide quantum dot material, cadmium sulfide quantum dot material and composite quantum dot material, and the particle size of the copper sulfide quantum dot material, the zinc sulfide quantum dot material and the cadmium sulfide quantum dot material is less than 20nm.

[0007] Optionally, the raw materials for preparing the composite quantum dot material include the copper sulfide quantum dot material, the zinc sulfide quantum dot material, the cadmium sulfide quantum dot material and ethylene glycol, and the mass ratio of the copper sulfide quantum dot material, the zinc sulfide quantum dot material, the cadmium sulfide quantum dot material and the ethylene glycol is (0.05-0.2): (0.05-0.2): (0.05-0.2): (50-60); and / or,

[0008] Preferably, the preparation method of the composite quantum dot material comprises the following steps: adding the copper sulfide quantum dot material, the zinc sulfide quantum dot material, and the cadmium sulfide quantum dot material to a solution containing anhydrous ethanol and ethylene glycol, dispersing by magnetic stirring, obtaining a solid product by centrifugal separation, placing the solid product in a vacuum drying oven, and drying it at 50 to 70° C. for 5 to 7 hours to obtain a partially reduced composite quantum dot material; wherein the mass of the ethylene glycol is 2.5 to 4.5 times the mass of the anhydrous ethanol.

[0009] Further preferably, the mass ratio of the copper sulfide quantum dot material, the zinc sulfide quantum dot material, the cadmium sulfide quantum dot material and the ethylene glycol is 0.1:0.1:0.1:55.5.

[0010] Preferably, the mass ratio of the organic binder resin, the curing agent and the quantum dot material is 4:6:(0.005-0.05).

[0011] Preferably, the quantum dot material includes zinc sulfide quantum dot material, and the mass ratio of the organic binder resin, the curing agent and the quantum dot material is 4:6:0.005.

[0012] Preferably, the quantum dot material includes cadmium sulfide quantum dot material, and the mass ratio of the organic binder resin, the curing agent and the quantum dot material is 4:6:0.05.

[0013] The organic bonding resin includes epoxy resin, and the curing agent includes one of an amine curing agent, an acid anhydride curing agent and a resin curing agent.

[0014] Optionally, the method for preparing the copper sulfide quantum dot material comprises the following steps:

[0015] Add the copper source into deionized water, stir for 10 to 50 minutes, add the surfactant, continue stirring for 0.5 to 2.0 hours, add the sulfur source, and stir for another 20 to 60 minutes to obtain a mixed solution;

[0016] The mixed solution is transferred to a reaction kettle, stirred and reacted at 120-200° C. for 5-20 hours, cooled to room temperature, and the reactant is taken out and filtered, washed and dried to obtain the copper sulfide quantum dot material.

[0017] Optionally, the mass ratio of the copper source, the deionized water, the surfactant and the sulfur source is (0.1-0.8): (50-70): (0.05-0.15): (0.1-0.3); and / or,

[0018] The copper source comprises copper nitrate trihydrate, the sulfur source comprises thiourea, and the surfactant comprises one of polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide; and / or,

[0019] The reactant is washed with deionized water and anhydrous ethanol, and the washed reactant is placed in a vacuum drying oven and dried at 40 to 60° C. for 8 to 12 hours.

[0020] Optionally, the method for preparing the zinc sulfide quantum dot material comprises the following steps:

[0021] Add a zinc source to deionized water, control the temperature to 10-50°C, stir for 5-20 minutes, adjust the temperature to 30-80°C, add mercaptopropionic acid, stir and react for 30-60 minutes, adjust the temperature to 80-100°C, add a sodium sulfide aqueous solution, adjust the pH value to 7.5-9.0, stir for 2-4 hours, add anhydrous ethanol, a white precipitate appears, and obtain a solid product by centrifugation. Wash and dry the solid product to obtain the zinc sulfide quantum dot material.

[0022] Optionally, the mass ratio of the zinc source, the deionized water, the mercaptopropionic acid, the sodium sulfide aqueous solution and the anhydrous ethanol is (5-8): (110-150): (6-12): (30-50): (140-200); and / or,

[0023] The zinc source comprises zinc acetate; and / or,

[0024] The sodium sulfide aqueous solution is added in small amounts and multiple times, and the preparation method of the sodium sulfide aqueous solution comprises: dissolving sodium sulfide in deionized water, stirring sufficiently, and obtaining a sodium sulfide aqueous solution with a concentration of 0.1 to 0.2 g / ml; and / or,

[0025] The pH value is adjusted using a sodium hydroxide aqueous solution with a concentration of 1.5 to 2.5 mol / L.

[0026] Optionally, the method for preparing the cadmium sulfide quantum dot material comprises the following steps:

[0027] Adding a sulfur source, a cadmium source and a surfactant into distilled water and stirring thoroughly to obtain a mixed solution;

[0028] The mixed solution is added into a reaction kettle, stirred and reacted at 140-180° C. for 2-4 hours, cooled to room temperature, and a solid product is obtained by centrifugal separation. The solid product is washed and dried to obtain the cadmium sulfide quantum dot material.

[0029] Optionally, the mass ratio of the sulfur source, the cadmium source, the surfactant and the distilled water is (1.2-2): (0.6-1.1): (0.05-0.15): (50-70); and / or,

[0030] The sulfur source includes sodium sulfide nonahydrate, the cadmium source includes cadmium sulfate, and the surfactant includes polyvinyl pyrrolidone; and / or,

[0031] The solid product is washed with deionized water, and the washed solid product is placed in a vacuum drying oven and dried at 50 to 70° C. for 10 to 15 hours.

[0032] The present invention also proposes a method for preparing an anti-fouling and anti-corrosion coating based on quantum dot materials, comprising the following steps: providing an organic binding resin, a curing agent and a quantum dot material, adding the quantum dot material to the curing agent, ultrasonically dispersing, adding the organic binding resin, fully stirring, vacuum degassing to obtain a coating, applying the coating on the surface of a substrate, and curing to form the anti-fouling and anti-corrosion coating based on the quantum dot material.

[0033] The present invention also proposes the use of any of the above-mentioned anti-fouling and anti-corrosion coatings based on quantum dot materials in the anti-fouling and anti-corrosion of hydraulic structures and marine equipment.

[0034] In the technical solution of the present invention, an organic binder resin is used as a matrix. The organic binder resin can be used as a carrier of quantum dot materials, disperse the quantum dot materials better, and can also adhere to the substrate more stably. Copper sulfide quantum dot materials, zinc sulfide quantum dot materials, and cadmium sulfide quantum dot materials have excellent antibacterial properties. Dispersing them in an organic binder resin can improve the anti-corrosion and anti-fouling properties of the prepared coating. The particle size of copper sulfide quantum dot materials, zinc sulfide quantum dot materials, and cadmium sulfide quantum dot materials is less than 20nm. By utilizing the small size effect of quantum dot materials, the microscopic defects of the prepared coating can be effectively reduced, the compactness of the coating can be improved, and the coating can be guaranteed to have more stable anti-corrosion and anti-fouling properties. In addition, the amount of quantum dot materials used in the entire coating raw material is relatively small, which can better ensure that the quantum dot materials are more fully dispersed in the organic binder resin, and can also effectively reduce the secondary pollution caused by the quantum dot materials to the environment. The coating provided by the above technical solution of the present invention has excellent anti-corrosion and anti-fouling effects, and the protective effect is relatively stable and the service life is long. It can be well applied to the surfaces of substrates such as hydraulic structures and equipment materials in rivers, lakes and marine environments, and can effectively avoid biological fouling and corrosion problems on the surfaces of substrates such as metals and concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0036] Figure 1 (a) is a TEM morphology image of the copper sulfide quantum dot material prepared in Preparation Example 1 of the present invention;

[0037] Figure 1 (b) is a TEM morphology image of the zinc sulfide quantum dot material prepared in Preparation Example 2 of the present invention;

[0038] Figure 1 (c) is a TEM morphology image of the cadmium sulfide quantum dot material prepared in Preparation Example 3 of the present invention;

[0039] Figure 2 The electrochemical impedance spectrum of the pure epoxy resin coating prepared in Comparative Example 1 of the present invention was measured when it was immersed in a 3.5wt% NaCl solution for 60 days;

[0040] Figure 3 The electrochemical impedance spectra of the coating based on the copper sulfide quantum dot material prepared in Example 2 of the present invention are measured when immersed in a 3.5wt% NaCl solution for different time periods;

[0041] Figure 4 The electrochemical impedance spectra of the coatings based on copper sulfide quantum dot materials with different contents prepared in Examples 1 and 3 of the present invention were measured when immersed in a 3.5wt% NaCl solution for 60 days;

[0042] Figure 5 The electrochemical impedance spectra of the coatings based on zinc sulfide quantum dot materials with different contents prepared in Examples 4 to 6 of the present invention were measured when immersed in a 3.5wt% NaCl solution for 60 days;

[0043] Figure 6 The electrochemical impedance spectra of the coatings based on cadmium sulfide quantum dot materials with different contents prepared in Examples 7 to 9 of the present invention were measured when immersed in a 3.5wt% NaCl solution for 60 days;

[0044] Figure 7 The electrochemical impedance spectrum of the coating based on the composite quantum dot material prepared in Example 10 of the present invention was measured when it was immersed in a 3.5wt% NaCl solution for 60 days;

[0045] Figure 8 (a) is a scanning electron microscope image of the surface of a Q235 steel substrate after the pure epoxy resin coating prepared in Comparative Example 1 of the present invention was taken out and the coating was removed after being immersed in a 3.5wt% NaCl solution for 60 days;

[0046] Figure 8 (b) is an EDS elemental analysis diagram of the surface of a Q235 steel substrate after the pure epoxy resin coating prepared in Comparative Example 1 of the present invention was taken out and the coating was removed after being immersed in a 3.5wt% NaCl solution for 60 days;

[0047] Fig. 9 (a) is a scanning electron microscope image of the surface of a Q235 steel substrate after the coating based on the copper sulfide quantum dot material prepared in Example 2 of the present invention was taken out and the coating was removed after being immersed in a 3.5wt% NaCl solution for 60 days;

[0048] Fig. 9 (b) is a scanning electron microscope image of the surface of a Q235 steel substrate after the coating based on the zinc sulfide quantum dot material prepared in Example 5 of the present invention is taken out and the coating is removed after being immersed in a 3.5wt% NaCl solution for 60 days;

[0049] Fig. 9 (c) is a scanning electron microscope image of the surface of a Q235 steel substrate after the coating based on cadmium sulfide quantum dot material prepared in Example 8 of the present invention was taken out and removed after being immersed in a 3.5wt% NaCl solution for 60 days.

[0050] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0051] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0053] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features limited to "first" and "second" may explicitly or implicitly include at least one of the features. In addition, if "and / or" or "and / or" appears in the full text, its meaning includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or solutions that satisfy both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0054] Coating is currently a commonly used method for biofouling and corrosion protection. Coating forms a protective barrier on metal and concrete substrates, preventing corrosive media such as water and oxygen from diffusing to the surface of the material. However, after coating, there are inevitably microscopic defects such as pores and cracks inside the coating, and in the actual service environment, it is easy to have failure problems such as swelling, cracking, and peeling, which affects the protective effect of the coating.

[0055] In view of this, the present invention proposes an anti-fouling and anti-corrosion coating based on quantum dot materials and a preparation method and application thereof, so as to solve the problem that the existing coatings have poor anti-corrosion and anti-fouling effects.

[0056] In an embodiment of the present invention, the anti-fouling and anti-corrosion coating based on quantum dot material includes an organic binding resin, a curing agent and a quantum dot material, and the mass ratio of the organic binding resin, the curing agent and the quantum dot material is (3-5): (5-7): (0.005-0.05); wherein the quantum dot material includes at least one of copper sulfide quantum dot material, zinc sulfide quantum dot material, cadmium sulfide quantum dot material and composite quantum dot material, and the particle size of the copper sulfide quantum dot material, the zinc sulfide quantum dot material and the cadmium sulfide quantum dot material is less than 20 nm.

[0057] In the technical solution of the present invention, an organic binder resin is used as a matrix. The organic binder resin can be used as a carrier of quantum dot materials, disperse the quantum dot materials better, and can also adhere to the substrate more stably. Copper sulfide (CuS) quantum dot materials, zinc sulfide (ZnS) quantum dot materials, and cadmium sulfide (CdS) quantum dot materials have excellent antibacterial properties. Dispersing them in an organic binder resin can improve the anti-corrosion and anti-fouling properties of the prepared coating. The particle size of the copper sulfide quantum dot material, zinc sulfide quantum dot material, and cadmium sulfide quantum dot material is less than 20nm. By utilizing the small size effect of the quantum dot material, the microscopic defects of the prepared coating can be effectively reduced, the compactness of the coating can be improved, and the coating can be guaranteed to have more stable anti-corrosion and anti-fouling properties. In addition, the amount of quantum dot material used in the entire coating raw material is relatively small, which can better ensure that the quantum dot material is more fully dispersed in the organic binder resin, and can also effectively reduce the secondary pollution caused by the quantum dot material to the environment. The coating provided by the above technical solution of the present invention has excellent anti-corrosion and anti-fouling effects, and the protective effect is relatively stable and the service life is long. It can be well applied to the surfaces of substrates such as hydraulic structures and equipment materials in rivers, lakes and marine environments, and can effectively avoid biological fouling and corrosion problems on the surfaces of substrates such as metals and concrete.

[0058] It should be noted that the raw materials for preparing the composite quantum dot material include copper sulfide quantum dot material, zinc sulfide quantum dot material and cadmium sulfide quantum dot material. It is understandable that the coating prepared by using the composite quantum dot material also has a relatively stable anti-corrosion and anti-fouling effect.

[0059] Further, the raw materials for preparing the composite quantum dot material include the copper sulfide quantum dot material, the zinc sulfide quantum dot material, the cadmium sulfide quantum dot material and ethylene glycol, and the mass ratio of the copper sulfide quantum dot material, the zinc sulfide quantum dot material, the cadmium sulfide quantum dot material and the ethylene glycol is (0.05-0.2): (0.05-0.2): (0.05-0.2): (50-60); and / or,

[0060] The organic bonding resin includes epoxy resin, and the curing agent includes one of an amine curing agent, an acid anhydride curing agent and a resin curing agent.

[0061] By adopting the above technical solution, the composite quantum dot material formed by compounding copper sulfide quantum dot material, zinc sulfide quantum dot material and cadmium sulfide quantum dot material can significantly improve the anti-corrosion and anti-fouling performance of the coating compared with a single quantum dot material. The reason may be that the copper sulfide quantum dot material, zinc sulfide quantum dot material and cadmium sulfide quantum dot material are compounded according to a special ratio, which can play a good synergistic role, and ethylene glycol can reduce part of the divalent copper, part of the divalent zinc, and part of the divalent cadmium in the copper sulfide quantum dot material, zinc sulfide quantum dot material and cadmium sulfide quantum dot material into metal elements, and the antibacterial performance of metal elements is better. Therefore, the use of three specific quantum dot materials in a specific ratio has better anti-corrosion and anti-fouling performance than a single quantum dot material.

[0062] It should be noted that if the amount of ethylene glycol used is too little, the corresponding metal element reduced will be less, affecting the corrosion resistance and anti-fouling properties of the prepared coating; if the amount of ethylene glycol used is too much, more metal elements will be reduced, affecting the particle size of the prepared composite quantum dot material, which is likely to lead to an increase in particle size, reduce the dispersibility of the composite quantum dot material in the organic binder resin, and enhance the toxicity, affecting the corrosion resistance and anti-fouling properties of the prepared coating, and is also likely to cause secondary pollution to the environment.

[0063] It can be understood that the dosage ratio of copper sulfide quantum dot material, zinc sulfide quantum dot material and cadmium sulfide quantum dot material will also affect the anti-corrosion and anti-fouling properties of the prepared coating. The three quantum dot materials are used in different ratios, and the anti-corrosion and anti-fouling properties of the prepared coating are different. The copper sulfide quantum dot material, zinc sulfide quantum dot material and cadmium sulfide quantum dot material of the present invention are compounded according to a special ratio, which can better ensure the anti-corrosion and anti-fouling effects of the coating, so as to better meet the use requirements.

[0064] Organic bonding resins include epoxy resins, which have excellent physical and mechanical properties and electrical insulation properties, and have strong paint film adhesion.

[0065] Furthermore, the preparation method of the copper sulfide quantum dot material includes the following steps: adding a copper source to deionized water, stirring for 10 to 50 minutes, adding a surfactant, continuing to stir for 0.5 to 2.0 hours, adding a sulfur source, and stirring for another 20 to 60 minutes to obtain a mixed solution; transferring the mixed solution to a reactor, stirring and reacting at 120 to 200° C. for 5 to 20 hours, cooling to room temperature, taking out the reactant and filtering, washing and drying to obtain the copper sulfide quantum dot material.

[0066] By adopting the above technical scheme, the copper source is dissolved in deionized water, a surfactant is added, and then a sulfur source is added. The formed mixed solution is reacted at 120-200°C to obtain a copper sulfide quantum dot material with a particle size less than 20nm. The obtained copper sulfide quantum dot material has good anti-corrosion and anti-fouling properties.

[0067] Specifically, the mass ratio of the copper source, the deionized water, the surfactant and the sulfur source is (0.1-0.8): (50-70): (0.05-0.15): (0.1-0.3); and / or,

[0068] The copper source comprises copper nitrate trihydrate, the sulfur source comprises thiourea, and the surfactant comprises one of polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide; and / or,

[0069] The reactant is washed with deionized water and anhydrous ethanol, and the washed reactant is placed in a vacuum drying oven and dried at 40 to 60° C. for 8 to 12 hours.

[0070] Furthermore, the preparation method of the zinc sulfide quantum dot material comprises the following steps: adding a zinc source to deionized water, controlling the temperature to 10-50°C, stirring for 5-20 minutes, adjusting the temperature to 30-80°C, adding mercaptopropionic acid, stirring and reacting for 30-60 minutes, adjusting the temperature to 80-100°C, adding a sodium sulfide aqueous solution, adjusting the pH value to 7.5-9.0, stirring for 2-4 hours, adding anhydrous ethanol, a white precipitate appears, and obtaining a solid product by centrifugation. The solid product is washed and dried to obtain the zinc sulfide quantum dot material.

[0071] By adopting the above technical scheme, the zinc source can be fully dissolved in deionized water at 10-50°C, and the intermediate product can be well generated by adding mercaptopropionic acid at 30-80°C. At 80-100°C, a sodium sulfide aqueous solution is added, and the pH is adjusted to alkaline, and anhydrous ethanol is added to ensure the precipitation of precipitates. The precipitated precipitates are washed and dried to obtain zinc sulfide quantum dot materials with a particle size of less than 20nm. The prepared zinc sulfide quantum dot materials have good anti-corrosion and anti-fouling properties. By reasonably controlling the temperature conditions of each link, the particle size and performance of the prepared zinc sulfide quantum dot materials can be well guaranteed.

[0072] Specifically, the mass ratio of the zinc source, the deionized water, the mercaptopropionic acid, the sodium sulfide aqueous solution and the anhydrous ethanol is (5-8): (110-150): (6-12): (30-50): (140-200); and / or,

[0073] The zinc source comprises zinc acetate; and / or,

[0074] The sodium sulfide aqueous solution is added in small amounts and multiple times, and the preparation method of the sodium sulfide aqueous solution comprises: dissolving sodium sulfide in deionized water, stirring sufficiently, and obtaining a sodium sulfide aqueous solution with a concentration of 0.1 to 0.2 g / ml; and / or,

[0075] The pH value is adjusted using a sodium hydroxide aqueous solution with a concentration of 1.5 to 2.5 mol / L.

[0076] Furthermore, the preparation method of the cadmium sulfide quantum dot material comprises the following steps: adding a sulfur source, a cadmium source and a surfactant into distilled water, stirring sufficiently to obtain a mixed solution; adding the mixed solution into a reactor, stirring and reacting at 140 to 180° C. for 2 to 4 hours, cooling to room temperature, obtaining a solid product by centrifugal separation, washing and drying the solid product, and obtaining the cadmium sulfide quantum dot material.

[0077] By adopting the above technical scheme, a sulfur source, a cadmium source and a surfactant are dissolved in distilled water, and the formed mixed solution reacts at 140-180° C. to obtain a cadmium sulfide quantum dot material with a particle size less than 20 nm. The obtained cadmium sulfide quantum dot material has good anti-corrosion and anti-fouling properties.

[0078] Specifically, the mass ratio of the sulfur source, the cadmium source, the surfactant and the distilled water is (1.2-2): (0.6-1.1): (0.05-0.15): (50-70); and / or,

[0079] The sulfur source includes sodium sulfide nonahydrate, the cadmium source includes cadmium sulfate, and the surfactant includes polyvinyl pyrrolidone; and / or,

[0080] The solid product is washed with deionized water, and the washed solid product is placed in a vacuum drying oven and dried at 50 to 70° C. for 10 to 15 hours.

[0081] The present invention also proposes a method for preparing an anti-fouling and anti-corrosion coating based on quantum dot materials, comprising the following steps: providing an organic binding resin, a curing agent and a quantum dot material, adding the quantum dot material to the curing agent, ultrasonically dispersing, adding the organic binding resin, fully stirring, vacuum degassing to obtain a coating, applying the coating on the surface of a substrate, and curing to form the anti-fouling and anti-corrosion coating based on the quantum dot material.

[0082] In the technical solution of the present invention, the quantum dot material is dispersed in a curing agent, an organic binding resin is added, stirred, and vacuum degassed to obtain a coating, which is then applied to the surface of a substrate to form a dense anti-corrosion and anti-fouling coating after curing. The entire preparation process is simple and efficient.

[0083] The present invention also proposes the use of any of the above-mentioned anti-fouling and anti-corrosion coatings based on quantum dot materials in the anti-fouling and anti-corrosion of hydraulic structures and marine equipment.

[0084] The coating provided by the above technical solution of the present invention has excellent anti-corrosion and anti-fouling effects, and the protective effect is relatively stable and the service life is long. It can be well applied to the surface of substrates such as hydraulic structures and equipment materials in rivers, lakes and marine environments, and effectively avoids biological fouling and corrosion problems on the surface of substrates such as metals and concrete. In addition, the amount of quantum dot material used is relatively small, which can better ensure that the quantum dot material is more fully dispersed in the organic binder resin, and can also effectively reduce the secondary pollution caused by the quantum dot material to the environment.

[0085] The technical solution of the present application is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present application and are not used to limit the present application.

[0086] Preparation Example 1

[0087] A method for preparing a copper sulfide quantum dot material comprises the following steps:

[0088] 0.488 parts by weight of Cu(NO3)2·3H2O (copper nitrate trihydrate) was added to 60 parts by weight of deionized water, and the mixture was stirred magnetically for 30 minutes at room temperature (25°C) until the Cu(NO3)2·3H2O was fully dissolved. 0.1 parts by weight of hexadecyltrimethylammonium bromide (CTAB) was added, and the mixture was stirred magnetically for 1 hour to form a homogeneous solution. 0.153 parts by weight of thiourea (H2NCSNH3) was added, and the mixture was stirred magnetically for 40 minutes to obtain a mixed solution.

[0089] The mixed solution was transferred to a reactor, and the reaction was stirred at 160°C at a stirring rate of 100 rpm for 13 hours. After the reaction was completed, the mixture was cooled to room temperature (25°C). The reactants were taken out and centrifuged to obtain the product. The product was washed with deionized water 4 times and with anhydrous ethanol 4 times. The washed product was placed in a vacuum drying oven and dried at 50°C for 10 hours to obtain copper sulfide quantum dot material.

[0090] Preparation Example 2

[0091] A method for preparing a zinc sulfide quantum dot material comprises the following steps:

[0092] To a three-necked flask, 130 parts by weight of deionized water and 6.585 parts by weight of zinc acetate were respectively added, the temperature was controlled at 35°C, and the stirring rate was 100 rpm for 10 min. The temperature was controlled at 55°C, 9.552 parts by weight of mercaptopropionic acid were added, and the reaction was stirred at a stirring rate of 100 rpm for 45 min. The temperature was controlled at 95°C, 40 parts by weight of a 0.13 g / ml sodium sulfide aqueous solution were added, and the pH value of the solution was adjusted to 8.5 with a 2 mol / L sodium hydroxide aqueous solution. The solution was stirred at a stirring rate of 100 rpm for 3 h, and 158 parts by weight of anhydrous ethanol were added to produce a white precipitate. After centrifugation, a solid product was obtained, and the solid product was washed 3 times with anhydrous ethanol. The washed solid product was placed in a vacuum drying oven and dried at 60°C for 10 h to obtain a zinc sulfide quantum dot material.

[0093] The sodium sulfide aqueous solution is added in small amounts and multiple times, with 5 parts by weight added each time.

[0094] Preparation Example 3

[0095] A method for preparing a cadmium sulfide quantum dot material comprises the following steps:

[0096] 1.68 parts by weight of sodium sulfide nonahydrate (Na2S·9H2O), 0.90 parts by weight of cadmium sulfate (CdSO4), and 0.10 parts by weight of polyvinyl pyrrolidone (PVP, molecular weight of 58,000) were added to 60 parts by weight of distilled water, and magnetic stirring was performed for 10 minutes to obtain a mixed solution. The mixed solution was added to a reactor, stirred at 150°C at a stirring rate of 100 rpm for 3 hours, cooled to room temperature (25°C), and a solid product was obtained by centrifugal separation. The solid product was washed 3 times with deionized water, and the washed solid product was placed in a vacuum drying oven and dried at 60°C for 12 hours to obtain a cadmium sulfide quantum dot material.

[0097] Preparation Example 4

[0098] A method for preparing a composite quantum dot material comprises the following steps:

[0099] 0.1 weight parts of copper sulfide quantum dot material prepared in Preparation Example 1, 0.1 weight parts of zinc sulfide quantum dot material prepared in Preparation Example 2, and 0.1 weight parts of cadmium sulfide quantum dot material prepared in Preparation Example 3 were added to a solution containing 15.8 weight parts of anhydrous ethanol and 55.5 weight parts of ethylene glycol, and dispersed under magnetic stirring for 12 hours. A solid product was obtained by centrifugal separation, and the solid product was placed in a vacuum drying oven and dried at 60°C for 6 hours to obtain a partially reduced composite quantum dot material.

[0100] Performance test 1

[0101] The morphology and particle size of the copper sulfide quantum dot material prepared in Preparation Example 1, the zinc sulfide quantum dot material prepared in Preparation Example 2, and the cadmium sulfide quantum dot material prepared in Preparation Example 3 were observed using a FEI talos F200x G2 transmission electron microscope. The test results are as follows: Figure 1 As shown. Among them, Figure 1 Figure (a) corresponds to copper sulfide quantum dot material, Figure (b) corresponds to zinc sulfide quantum dot material, and Figure (c) corresponds to cadmium sulfide quantum dot material.

[0102] from Figure 1 As can be seen from Figures (a), (b) and (c) in the figure, the morphology of each quantum dot material is an irregular sphere with a particle size of about 10 nm.

[0103] Performance test 2

[0104] Antibacterial performance test of various quantum dot materials

[0105] Pseudomonas aeruginosa and Pseudomonas stutzeri were activated and cultured in a constant temperature incubator at 37°C for 2 days, wherein the culture medium of Pseudomonas aeruginosa included: 0.5g yeast extract, 1g peptone, 1g NaCl, and the pH value was 7; the culture medium of Pseudomonas stutzeri included: 0.5g / L K2HPO4, 0.5g / L NaNO3, 0.2g / L CaCl2, 0.5g / LMgSO4·7H2O, 0.5g / L (NH4)2SO4, 10g / L ammonium ferric citrate, and the pH value was 6.5.

[0106] 10 wt % pre-cultured bacterial culture was added to 0.85 wt % NaCl solution as a blank control group. On the basis of the blank control group, each experimental group was added with the corresponding quantum dot material prepared in Preparation Examples 1 to 4, and the concentration of each quantum dot material was 0.015 wt %.

[0107] The blank control group and each experimental group were placed in a 37°C constant temperature incubator for 24 hours, and the bacterial colony count was obtained by plate counting method. The test results are shown in Table 1. Before the test, the concentration of Pseudomonas aeruginosa in the blank control group and each experimental group was 3.0×10 7 cells / mL, and the concentration of Pseudomonas stutzeri was 4.8×10 5 cells / mL.

[0108] Before the experiment, all high temperature resistant glassware, 0.85wt% NaCl solution and bacterial culture medium were sterilized by high pressure at 121°C for more than 20 minutes.

[0109] Table 1 Bacterial colony count (unit: cells / mL)

[0110]

[0111]

[0112] According to the statistical analysis results of live bacteria in Table 1, compared with the blank control group, the copper sulfide quantum dot material (corresponding to Preparation Example 1), zinc sulfide quantum dot material (corresponding to Preparation Example 2), cadmium sulfide quantum dot material (corresponding to Preparation Example 3) and composite quantum dot material (corresponding to Preparation Example 4) with a concentration of 0.015wt% all have good antibacterial effects, and the counts of Pseudomonas aeruginosa and Pseudomonas stutzeri can be reduced by about 3 orders of magnitude, and the antibacterial effect of the composite quantum dot material is improved by more than 50% compared with the single quantum dot material.

[0113] Examples 1 to 3

[0114] Examples 1 to 3 use the copper sulfide quantum dot material prepared in Preparation Example 1 to prepare an antifouling and anticorrosion coating, and the thickness of the coating is 150 μm.

[0115] Example 1

[0116] A method for preparing an antifouling and anticorrosion coating based on quantum dot materials comprises the following steps:

[0117] 0.005 g of the copper sulfide quantum dot material prepared in Preparation Example 1 was provided, and 0.005 g of the copper sulfide quantum dot material was added to 6 g of T-31 epoxy resin curing agent, ultrasonically dispersed for 1.5 hours, 4 g of E51 epoxy resin was added, and after sufficient stirring, vacuum degassing was performed for 10 minutes to obtain a coating, and the coating was applied to the polished Q235 steel surface, cured at room temperature for 24 hours, and dried at 50° C. for 4 hours to obtain an anti-fouling and anti-corrosion coating based on quantum dot material, calculated as 0.05% CuS.

[0118] Example 2

[0119] This embodiment is based on the embodiment 1, and the difference is that the amount of copper sulfide quantum dot material used is 0.01 g, and the prepared antifouling and anticorrosion coating is calculated to be 0.1% CuS.

[0120] Example 3

[0121] This embodiment is based on the embodiment 1, and the difference is that the amount of copper sulfide quantum dot material used is 0.05 g, and the prepared antifouling and anticorrosion coating is calculated to be 0.5% CuS.

[0122] Embodiments 4 to 6

[0123] Examples 4 to 6 use the zinc sulfide quantum dot material prepared in Preparation Example 2 to prepare antifouling and anticorrosion coatings, and the thickness of the coatings is 150 μm.

[0124] Example 4

[0125] A method for preparing an antifouling and anticorrosion coating based on quantum dot materials comprises the following steps:

[0126] Provide 0.005g of the zinc sulfide quantum dot material prepared in Preparation Example 2, add 0.005g of the zinc sulfide quantum dot material to 6g of T-31 epoxy resin curing agent, ultrasonically disperse for 1.5h, add 4g of E51 epoxy resin, stir thoroughly, and vacuum degas for 10min to prepare a coating, apply the coating on the polished Q235 steel surface, cure at room temperature for 24h, and dry at 50°C for 4h to prepare an antifouling and anticorrosion coating based on quantum dot material, calculated as 0.05% ZnS.

[0127] Example 5

[0128] This embodiment is based on the embodiment 4, and the difference is that the amount of zinc sulfide quantum dot material used is 0.01 g, and the prepared antifouling and anticorrosion coating is calculated to be 0.1% ZnS.

[0129] Example 6

[0130] This embodiment is based on the embodiment 4, and the difference is that the amount of zinc sulfide quantum dot material used is 0.05 g, and the prepared antifouling and anticorrosion coating is calculated to be 0.5% ZnS.

[0131] Embodiments 7 to 9

[0132] Examples 7 to 9 use the cadmium sulfide quantum dot material prepared in Preparation Example 3 to prepare anti-fouling and anti-corrosion coatings, and the thickness of the coatings is 150 μm.

[0133] Example 7

[0134] A method for preparing an antifouling and anticorrosion coating based on quantum dot materials comprises the following steps:

[0135] Provide 0.005g of the cadmium sulfide quantum dot material prepared in Preparation Example 3, add 0.005g of the cadmium sulfide quantum dot material to 6g of T-31 epoxy resin curing agent, ultrasonically disperse for 1.5h, add 4g of E51 epoxy resin, stir thoroughly, and vacuum degas for 10min to prepare a coating, apply the coating on the polished Q235 steel surface, cure at room temperature for 24h, and dry at 50°C for 4h to prepare an anti-fouling and anti-corrosion coating based on quantum dot material, calculated as 0.05% CdS.

[0136] Example 8

[0137] This embodiment is based on the embodiment 7, and the difference is that the amount of cadmium sulfide quantum dot material used is 0.01 g, and the prepared antifouling and anticorrosion coating is calculated to be 0.1% CdS.

[0138] Example 9

[0139] This embodiment is based on the embodiment 7, and the difference is that the amount of cadmium sulfide quantum dot material used is 0.05 g, and the prepared antifouling and anticorrosion coating is calculated to be 0.5% CdS.

[0140] Example 10

[0141] Example 10 uses the composite quantum dot material prepared in Preparation Example 4 to prepare an anti-fouling and anti-corrosion coating, and the thickness of the coating is 150 μm.

[0142] Example 10

[0143] A method for preparing an antifouling and anticorrosion coating based on quantum dot materials comprises the following steps:

[0144] Provide 0.05 g of the composite quantum dot material prepared in Preparation Example 4, add 0.005 g of the composite quantum dot material to 6 g of T-31 epoxy resin curing agent, ultrasonically disperse for 1.5 hours, add 4 g of E51 epoxy resin, stir thoroughly, and vacuum degas for 10 minutes to obtain a coating, apply the coating on the polished Q235 steel surface, cure at room temperature for 24 hours, and dry at 50°C for 4 hours to obtain an anti-fouling and anti-corrosion coating based on quantum dot material.

[0145] Comparative Example 1

[0146] A method for preparing an antifouling and anticorrosion coating comprises the following steps:

[0147] 6 g of T-31 epoxy resin curing agent was added to 4 g of E51 epoxy resin, and after sufficient stirring, vacuum degassing was performed for 10 minutes to obtain a coating. The coating was applied to the polished Q235 steel surface, cured at room temperature for 24 hours, and dried at 50°C for 4 hours to obtain an antifouling and anticorrosion coating.

[0148] Performance test 3

[0149] Anti-corrosion performance test of each coating

[0150] The electrochemical impedance of the antifouling and anticorrosion coatings prepared in Examples 1 to 10 and Comparative Example 1 in a 3.5 wt% NaCl solution was detected using a Gamry electrochemical workstation. The test used a classic three-electrode system, with the antifouling and anticorrosion coatings prepared in Examples 1 to 10 and Comparative Example 1 as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum sheet as the auxiliary electrode. The test time was 60 days, and the measured electrochemical impedance spectrum was as follows: Figures 2 to 7 shown.

[0151] After 60 days, the antifouling and anticorrosion coating samples corresponding to Example 2, Example 5, Example 8, and Comparative Example 1 were taken out. After the coating corresponding to Comparative Example 1 was peeled off, the surface morphology of the Q235 steel substrate was observed using a JSM-IT200A scanning electron microscope and EDS element analysis. Before observation, the sample surface was gold-sprayed using a JYSC-100 ion sputtering instrument. The test results are as follows: Figure 8 After peeling off the coatings corresponding to Example 2, Example 5 and Example 8, the surface morphology of Q235 steel was observed using a JSM-IT200A scanning electron microscope. Before observation, the sample surface was subjected to gold spraying using a JYSC-100 ion sputtering instrument. The test results are shown in FIG. Fig. 9 shown.

[0152] Depend on Figure 2 It can be seen that the impedance modulus of the pure epoxy resin coating prepared in Comparative Example 1 has dropped to 2.7×10 6 Ω·cm 2 , indicating that the water permeability of the coating has increased and the anti-corrosion performance of the Q235 steel substrate has been lost. Figures 3 to 6 It can be seen that the impedance modulus of the quantum dot coatings corresponding to Examples 1 to 10 remains at 10 when immersed in a 3.5wt% NaCl solution for 60 days. 9 Ω·cm 2 , has very excellent anti-corrosion properties.

[0153] from Figure 3 It can also be seen that the impedance value of the coating based on copper sulfide quantum dot material hardly changes over time, indicating that the coating prepared by the present invention has very stable anti-corrosion performance. Figures 4 to 6 It can be seen that when the dosage of each quantum dot material is 0.05wt% of the total mass of the corresponding epoxy resin and curing agent, the coating has excellent anti-corrosion performance, indicating that when the dosage of each quantum dot is low, it can still play a good anti-corrosion effect. The coating of the present invention has a better application prospect.

[0154] Will Figure 7 and Figures 3 to 6 By comparison, the impedance value of the coating based on the composite quantum dot material has increased significantly, and it has better anti-corrosion performance, indicating that copper sulfide quantum dot material, zinc sulfide quantum dot material and cadmium sulfide quantum dot material have a synergistic effect in anti-corrosion performance.

[0155] Figure 8 (a) is the surface morphology of the pure epoxy resin coating after being immersed in 3.5wt% NaCl solution for 60 days and then removing the coating. Figure 8(a) It can be seen that obvious corrosion products appear on the surface of Q235 steel substrate. Figure 8 (b) shows that the surface of the Q235 steel substrate is enriched with oxygen and chlorine, indicating that the coating has lost its anti-corrosion performance. Fig. 9 It can be seen that after the coatings corresponding to Example 2, Example 5 and Example 8 are peeled off, clear mechanical polishing scratches are visible on the surface of the corresponding Q235 steel substrate, and no corrosion products are found, indicating that the coating made based on quantum dot materials helps to improve the density of the coating and can effectively hinder the diffusion of corrosive media to the surface of the substrate, thereby improving the corrosion resistance of the coating.

[0156] Performance test 4

[0157] Antifouling performance test of each coating

[0158] Pseudomonas aeruginosa and Pseudomonas stutzeri were activated and cultured in a constant temperature incubator at 37°C for 2 days, wherein the culture medium of Pseudomonas aeruginosa included: 0.5g yeast extract, 1g peptone, 1g NaCl, and the pH value was 7; the culture medium of Pseudomonas stutzeri included: 0.5g / L K2HPO4, 0.5g / L NaNO3, 0.2g / L CaCl2, 0.5g / LMgSO4·7H2O, 0.5g / L (NH4)2SO4, 10g / L ammonium ferric citrate, and the pH value was 6.5.

[0159] The pre-cultured bacteria were added to a 3.5 wt % NaCl solution as a test solution, wherein the concentration of Pseudomonas aeruginosa in the prepared test solution was 3.2×10 7 cells / mL, and the concentration of Pseudomonas stutzeri was 4.5×10 6 cells / mL.

[0160] The coatings prepared in Example 2, Example 5, Example 8, Example 10 and Comparative Example 1 were placed in test solutions containing Pseudomonas aeruginosa and Pseudomonas stutzeri, respectively. The thickness of each coating was 150 μm and the area was 5 cm 2 After being immersed in an environment of 37°C for 60 days, the samples were taken out and the bacterial colony counts on the surfaces of the coatings were obtained by plate counting method. The test results are shown in Table 2 below.

[0161] Table 2 Bacterial colony counts (unit: cells / cm 2 )

[0162] Pseudomonas aeruginosa Pseudomonas stutzeri Comparative Example 1 <![CDATA[7.5×10 7 ]]> <![CDATA[7.9×10 7 ]]> Example 2 <![CDATA[2.6×10 3 ]]> <![CDATA[3.1×10 3 ]]> Example 5 <![CDATA[3.8×10 3 ]]> <![CDATA[4.2×10 3 ]]> Example 8 <![CDATA[1.9×10 3 ]]> <![CDATA[2.1×10 3 ]]> Example 10 <![CDATA[1.7×10 2 ]]> <![CDATA[2.6×10 2 ]]>

[0163] It can be seen from the statistical results in Table 2 that after immersion in 3.5wt.% sodium chloride solution for 60 minutes, the surface fouling bacteria of pure epoxy resin coating (Comparative Example 1), copper sulfide quantum dot coating (Example 2), zinc sulfide quantum dot coating (Example 5), cadmium sulfide quantum dot coating (Example 8), and composite quantum dot coating (Example 10) are compared. The copper sulfide quantum dot coating, zinc sulfide quantum dot coating, cadmium sulfide quantum dot coating and composite quantum dot coating prepared by the present invention all have excellent anti-fouling performance, and the surface fouling bacteria are reduced by more than 4 orders of magnitude, and the anti-fouling efficiency is high. Among them, the anti-fouling efficiency of the composite quantum dot coating is higher, and the amount of surface fouling bacteria is reduced by one order of magnitude compared with the CuS quantum dot coating, ZnS quantum dot coating, and CdS quantum dot coating, which further illustrates that the CuS quantum dot material, ZnS quantum dot material and CdS quantum dot material have synergistic antibacterial performance, and the anti-fouling performance of the coating can be significantly improved through synergy.

[0164] The above are only preferred embodiments of the present application, and do not limit the scope of the present application. For those skilled in the art, the present application may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the scope of the patent protection of the present application.

Claims

1. An antifouling and anticorrosion coating based on quantum dot materials, characterized in that: It comprises an organic binding resin, a curing agent and a quantum dot material, and the mass ratio of the organic binding resin, the curing agent and the quantum dot material is (3-5): (5-7): (0.005-0.05); Among them, the quantum dot material includes at least one of copper sulfide quantum dot material, zinc sulfide quantum dot material, cadmium sulfide quantum dot material and composite quantum dot material, and the particle size of the copper sulfide quantum dot material, the zinc sulfide quantum dot material and the cadmium sulfide quantum dot material is less than 20nm.

2. The antifouling and anticorrosion coating based on quantum dot material according to claim 1, characterized in that: The raw materials for preparing the composite quantum dot material include the copper sulfide quantum dot material, the zinc sulfide quantum dot material, the cadmium sulfide quantum dot material and ethylene glycol, and the mass ratio of the copper sulfide quantum dot material, the zinc sulfide quantum dot material, the cadmium sulfide quantum dot material and the ethylene glycol is (0.05-0.2): (0.05-0.2): (0.05-0.2): (50-60); and / or, The organic bonding resin includes epoxy resin, and the curing agent includes one of an amine curing agent, an acid anhydride curing agent and a resin curing agent.

3. The antifouling and anticorrosion coating based on quantum dot material according to claim 1, characterized in that: The preparation method of the copper sulfide quantum dot material comprises the following steps: Add the copper source into deionized water, stir for 10 to 50 minutes, add the surfactant, continue stirring for 0.5 to 2.0 hours, add the sulfur source, and stir for another 20 to 60 minutes to obtain a mixed solution; The mixed solution is transferred to a reaction kettle, stirred and reacted at 120-200° C. for 5-20 hours, cooled to room temperature, and the reactant is taken out and filtered, washed and dried to obtain the copper sulfide quantum dot material.

4. The antifouling and anticorrosion coating based on quantum dot material as claimed in claim 3, characterized in that: The mass ratio of the copper source, the deionized water, the surfactant and the sulfur source is (0.1-0.8): (50-70): (0.05-0.15): (0.1-0.3); and / or, The copper source comprises copper nitrate trihydrate, the sulfur source comprises thiourea, and the surfactant comprises one of polyvinyl pyrrolidone and hexadecyltrimethylammonium bromide; and / or, The reactant is washed with deionized water and anhydrous ethanol, and the washed reactant is placed in a vacuum drying oven and dried at 40 to 60° C. for 8 to 12 hours.

5. The antifouling and anticorrosion coating based on quantum dot material according to claim 1, characterized in that: The preparation method of the zinc sulfide quantum dot material comprises the following steps: Add a zinc source to deionized water, control the temperature to 10-50°C, stir for 5-20 minutes, adjust the temperature to 30-80°C, add mercaptopropionic acid, stir and react for 30-60 minutes, adjust the temperature to 80-100°C, add a sodium sulfide aqueous solution, adjust the pH value to 7.5-9.0, stir for 2-4 hours, add anhydrous ethanol, a white precipitate appears, and obtain a solid product by centrifugation. Wash and dry the solid product to obtain the zinc sulfide quantum dot material.

6. The antifouling and anticorrosion coating based on quantum dot material according to claim 5, characterized in that: The mass ratio of the zinc source, the deionized water, the mercaptopropionic acid, the sodium sulfide aqueous solution and the anhydrous ethanol is (5-8): (110-150): (6-12): (30-50): (140-200); and / or, The zinc source comprises zinc acetate; and / or, The sodium sulfide aqueous solution is added in small amounts and multiple times, and the preparation method of the sodium sulfide aqueous solution comprises: dissolving sodium sulfide in deionized water, stirring sufficiently, and obtaining a sodium sulfide aqueous solution with a concentration of 0.1 to 0.2 g / ml; and / or, The pH value is adjusted using a sodium hydroxide aqueous solution with a concentration of 1.5 to 2.5 mol / L.

7. The antifouling and anticorrosion coating based on quantum dot material according to claim 1, characterized in that: The preparation method of the cadmium sulfide quantum dot material comprises the following steps: Adding a sulfur source, a cadmium source and a surfactant into distilled water and stirring thoroughly to obtain a mixed solution; The mixed solution is added into a reaction kettle, stirred and reacted at 140-180° C. for 2-4 hours, cooled to room temperature, and a solid product is obtained by centrifugal separation. The solid product is washed and dried to obtain the cadmium sulfide quantum dot material.

8. The antifouling and anticorrosion coating based on quantum dot material according to claim 7, characterized in that: The mass ratio of the sulfur source, the cadmium source, the surfactant and the distilled water is (1.2-2): (0.6-1.1): (0.05-0.15): (50-70); and / or, The sulfur source includes sodium sulfide nonahydrate, the cadmium source includes cadmium sulfate, and the surfactant includes polyvinyl pyrrolidone; and / or, The solid product is washed with deionized water, and the washed solid product is placed in a vacuum drying oven and dried at 50 to 70° C. for 10 to 15 hours.

9. A method for preparing an antifouling and anticorrosion coating based on quantum dot materials, characterized in that: The following steps are involved: An organic binding resin, a curing agent and a quantum dot material are provided, the quantum dot material is added to the curing agent, ultrasonically dispersed, the organic binding resin is added, fully stirred, vacuum degassed to obtain a coating, the coating is applied to a substrate surface, and cured to form the antifouling and anticorrosion coating based on the quantum dot material.

10. Use of the antifouling and anticorrosion coating based on quantum dot materials as claimed in any one of claims 1 to 8 in the antifouling and anticorrosion of hydraulic structures and marine equipment.

Citation Information

Patent Citations

  • Anti-corrosion and anti-fouling nano composite material containing graphene-based nano material / zinc oxide quantum dots and application thereof

    CN114015321A

  • Preparation method of cuprous sulfide-copper sulfide nanocomposite

    CN115957780A